Generalised relative defects of meromorphic function - Indrajit Lahiri ,; Nil Ratan Battacharjee, (Universiti Kebangsaan Malaysia, 1996)
Introducing the notion of generalised relative defect we compare it with the Nevanlinna defect of a meromorphic function.